Adoption of Critical View of Safety versus Infundibular Technique in Laparoscopic Cholecystectomy: A comparative study (Iraqi Journal of Medical Sciences, 2022)
Background: Laparoscopic cholecystectomy (LC) is the most common elective surgery performed by a general surgeon. Although being a routine procedure, classical pitfalls as misperception of intraoperative anatomy is one of the leading causes of bile duct injuries (BDI). The critical view of safety (CVS) in LC can be a new safe technique for identification of anatomy to reduce such a risk.Objective: To assess the efficacy of CVS in LC compared with the traditional infundibular technique.Methods: This comparative study included 344 patients who suffered from symptomatic gall stones. Patients have been grouped into two groups: group A (172 patients) operated utilizing the traditional infundibular technique and group B (172 patients) by CVS technique. Preoperative patient assessment, operating time and intraoperative and postoperative events including hospital stay, were recorded. Those patients who were unfit and or with bleeding disorders were excluded from the study. Postoperatively, patients were assessed using clinical examination for the possible complications.Results: The main perioperative complications bleeding and bile leak were significantly reported in infundibular group 6.98% and 9.88% respectively compared to 0.58% and 1.74% in CVS group respectively. Postoperatively, both intra-abdominal collection and bile leak were significantly lower in CVS group (1.16% and 1.74%, respectively) than in infundibular group (7.58% and 6.98%, respectively). Furthermore, hospital stay was significantly less in CVS group (1.8±2.7 days) compared to infundibular group (3.14±2.8 days).Conclusion: Using the CVS is associated with shorter operative time, less frequent peri- and postoperative complications and shorter hospital stay compared with infundibular technique.Keywords: Laparoscopic cholecystectomy, critical view of safety (CVS) Citation: Abdulhassan BA, Noman ZK, Hamdawi MA. Adoption of critical view of safety versus infundibular technique in laparoscopic cholecystectomy: A comparative study. Iraqi JMS. 2022; 20(2): 262-268. doi: 10.22578/IJMS.20.2.14
Keywords: Laparoscopic cholecystectomy; critical view of safety CVS